HUBUNGAN KUALITAS TIDUR DENGAN TINGKAT KEBUGARAN JASMANI TERHADAP MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA ANGKATAN 2019 - PUTRA, AIDIL TRI ERIA; ANSYARI, DEDI (JURNAL ILMIAH SIMANTEK, 2024)
Physical fitness is a description of a person's physical condition or functional condition in carrying out various jobs or daily activities. The higher the level of physical fitness, the better the physical condition, so that they are able to do various jobs or workloads given and will be successful in completing the work. That way the ability or level of productivity is higher. To be able to do work or daily activities well, it takes good physical fitness as well. Healthy living habits are one of the factors that must be considered and can affect physical fitness, one of these habits is sleep. Sleep is a basic human need. Every human being needs time to rest and sleep to be able to restore stamina or good body condition so that they can do various jobs or daily activities. The purpose this research are to determine the relationship between sleep quality and physical fitness level for students of the Faculty of Medicine, University of Muhammadiyah North Sumatra, Class of 2019. Using an analytical method with a cross sectional approach, that is, each research subject will only be used once to determine the relationship between sleep quality and fitness level. physical student of the Faculty of Medicine, University of Muhammadiyah North Sumatra. The data of this study were obtained using the PSQI questionnaire and the Harvard Step Test. Data analysis using Chi Square test. The results showed that most of the respondents had poor sleep quality (64.4%) and most of them had a very poor level of physical fitness (57.8%). And there is a relationship between sleep quality and physical fitness level (p = 0.001).